Investigating the effectiveness of JBS Module on higher order thinking skills among Year 5 students: a quasi-experimental approach - Mat, Hamidah; Al Ajmi, Mohammed (Academica Press Solutions, 2023)
The goal of this study is to ascertain how the Jom Bijak Sains Module affects fifth-year students' higher-order thinking abilities. A quasi-experimental approach with pre- and post-tests is used in the investigation. This module's development is based on ADDIE models, which include the phases of analysis, design, implementation, evaluation, and implementation. 33 students from the treatment group and 33 from the control group were randomly chosen as the samples. Pre-test and post-test are the instruments that are employed. The study demonstrates that the treatment group showed greater achievement in scores compared to the control group, as evidenced by the significant difference between the treatment and control groups. The results also showed that no significant differences were observed in students' higher-order thinking skills when considering gender. The Jom Bijak Sains module, helps Year 5 students develop their higher-order thinking skills and abilities. The results of the study indicate that year 5 students' Higher Order Thinking Skills can be improved by using this module in primary school science classes.